2017
DOI: 10.15832/ankutbd.447616
|View full text |Cite
|
Sign up to set email alerts
|

ContacToxicity of Six Plant Extracts to Different Larval Stages of Colorado Potato Beetle (Leptinotarsa decemlineata SAY (Col: Chrysomelidae))

Abstract: Discovery of new eco-friendly methods for insect pest management is very important in integrated pest management program. Contact toxicity of six plant extracts i.e. Acanthus dioscoridis L. (Acanthaceae), Achillea millefolium L. (Asteraceae), Bifora radians Bieb. (Apiaceae), Heracleum platytaenium Boiss (Apiaceae), Humulus lupulus L. (Cannabaceae) and Phlomoides tuberosa (L.) Moench (Lamiaceae), were tested on the 1 st to 4 th instar larvae of Colorado potato beetle (Leptinotarsa decemlineata Say. (Coleoptera:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…In another similar experiment, extracts of Acanthus dioscoridis L., Achillea millefolium L., Bifora radians, Heracleum platytaenium Boiss, H. lupulus, and Phlomoides tuberosa L. were tested against different larval stages for two days. For second to fourth instar larval stages, H. lupulus and H. platytenium reached the highest CPB mortality rate while the first larval stage was more susceptible [75].…”
Section: Use Of the Plant Extracts And Botanical Insecticidesmentioning
confidence: 96%
See 2 more Smart Citations
“…In another similar experiment, extracts of Acanthus dioscoridis L., Achillea millefolium L., Bifora radians, Heracleum platytaenium Boiss, H. lupulus, and Phlomoides tuberosa L. were tested against different larval stages for two days. For second to fourth instar larval stages, H. lupulus and H. platytenium reached the highest CPB mortality rate while the first larval stage was more susceptible [75].…”
Section: Use Of the Plant Extracts And Botanical Insecticidesmentioning
confidence: 96%
“…Acanthus dioscoridis L. [74,75] protects potato leaves 1-2 days in field Achillea millefolium L. [74,75] protects potato leaves 1-2 days in field Aesculus hippocastanum L. [76] successful in field studies Alnus glutinosa L. [76] successful in field studies Arctium lappa L. [74] efficient, especially mid-high doses Armoracia rusticana L. [19] weak effects in field trials Artemisia absinthium L. [77] successful in field studies Artemisia vulgaris L. [5,77] efficient, also against CPB eggs…”
Section: Plant Extracts and Botanical Insecticidementioning
confidence: 99%
See 1 more Smart Citation
“…The larvae were then placed in 90-mm plastic Petri dishes with sufficient potato leaves in the incubator (Nüve EN500). After 24 h, the larvae that did not react when touched their body gently with a soft brush were considered to be dead (Alkan et al, 2017). Resistance ratio (RR) was classified according to Lee et al, (1999): RR < 2, no resistance or very low resistance; RR = 2-5, low level resistance; RR=5-10, moderate level resistance; and RR > 10, high level resistance.…”
Section: Insecticides Applicationmentioning
confidence: 99%
“…This may be interpreted as a decrease in activity of the essential oil as the larval period progresses depending on the physiology of the insect. Alkan et al (2017) found that the activity changed due to the larval period in the study conducted with Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae). Similarly, Karakoç and Gökçe (2012) were reported that as larval stages progressed activity was decreased.…”
Section: Chemical Composition and Insecticidal Activity Of Fractionsmentioning
confidence: 99%